Determinants of Long-Term Orientation in Buyer-Seller Relationships - Ganesan, Shankar (Journal of Marketing, 1994)
Marketing managers must know the time orientation of a customer to select and use marketing tools that correspond to the time horizons of the customer. Insufficient understanding of a customer's time orientation can lead to problems, such as attempting a relationship marketing when transaction marketing is more appropriate. The author suggests that long-term orientation in a buyer/seller relationship is a function of two main factors: mutual dependence and the extent to which they trust one another. Dependence and trust are related to environmental uncertainty, transaction-specific investments, reputation, and satisfaction in a buyer/seller relationship. The framework presented here is tested with 124 retail buyers and 52 vendors supplying to those retailers. The results indicate that trust and dependence play key roles in determining the long-term orientation of both retail buyers and their vendors. The results also indicate that both similarities and differences exist across retailers and vendors with respect to the effects of several variables on long-term orientation, dependence, and trust.